Remaja Masjid Agung Baitul Ghafur Aceh Barat Daya; Pembinaan Keagamaan Generasi Z - M. Juli Nawawi; Kusmawati Hatta; Suriati N; Mahdalil Ikram (Departement of Mathematics Education, 2024)
This research examines the role of the Baitul Ghafur Grand Youth Mosque (RMA) in Southwest Aceh in the religious development of Generation Z. Generation Z, who live in the digital era and globalisation, are vulnerable to negative influences from technological developments and global culture. This study used a qualitative approach with direct observation, interviews, and documentation techniques to collect data. The data was analysed descriptively to explore the effectiveness of religious development programmes implemented by the RMA. The results showed that RMA has a significant role in fortifying generation Z from the adverse effects of globalisation by providing a platform for spiritual and moral development. However, challenges such as lack of youth participation and external support still hinder the implementation of these programmes. This research underscores the important role of mosques in maintaining the continuity of religious values amidst rapid globalisation. The concerted effort to optimise religious formation programmes in RMAs can serve as a model for similar efforts elsewhere, ensuring that Generation Z can grow up as spiritually and morally strong individuals to face the challenges of modern times.